OP0281 Kawasaki Disease in France: Incomplete Forms Are the Most Frequent and Are Associated with High Frequency of Cardiac Complications. (10th June 2014) - Koné paut, I.; Darce Bello, M.; Brochard, K.; Merlin, E.; Launay, E.; Lechevalier, P.; Uettwiller, F.; Brosset, P.; Boralevi, F.; Di-filippo, S.; Gajdos, V.; Madhi, F.; et al.
Abstract : Background: KD is the main vasculitis affecting children before 5 years and the leading cause of acquired heart disease in childhood. The epidemiologic characteristics of KD are few reported in Europe and especially in France within a population from different ethnic backgrounds. Even IVIG is still the standard treatment of KD; the management of patients at risk for cardiac complications may change toward reinforced (and new) therapeutic approaches. Objectives: Kawanet is a clinical and biological data repository aimed to define the epidemiological characteristics of KD, in France. Kawanet will compare clinical characteristics between distinct ethnic backgrounds and will define risk factors for resistance to standard treatment (IVIG) and for cardiac complications Methods: Targeted institutional physicians received information on a national registry for KD. All patients suspected with KD and seen since January 2011 were eligible to enter the study. An eCRF was implemented in a web secured database (CLEANWeb). IRB approval and authorization for data storage were obtained. Results: 419 cases were entered into the registry and complete information was available for 351 of them, in January 2014. Patients (57% males/43% females) were enrolled by 77 physicians from 52 centres: they originated from 5 main ethnical backgrounds: 67% European Caucasian, 15% afro-Caribbean, 13% Eastern Caucasian or North African, 4% Asian and 1% of mixed ancestry. The median age at diagnosis was 2.4y (3m-26y). A family history of KD was present in 5 patients. The clinical symptoms were (%): conjunctivitis 85, cheilitis 83, diffuse exanthema 74, fever ≥5 days 63, oral erythema 61, modification of the extremities 57, cervical adenopathy 49, oedema 47, raspberry tongue 45, desquamation 40, seat erythema 26 and perineal desquamation 17. Cardiac complications were reported in 186/328 patients (42%): coronary dilatation 28%, pericarditis 17%, coronary aneurysm 4%, and myocarditis 3%. At diagnosis of 351 patients: 135 had complete KD according to the AAC definition, 56 were incomplete, 118 doubtful and 42 not classified. 327/331 (99%) patients received IVIG, 20% (n=64) required 2 courses, and 5 patients 3 courses. 11% required steroids, 93% received Aspirin and 1 Anti-TNF. The mean delay between fever onset and treatment was 6 days. Conclusions: The awareness on KD appears very high in France, even the completed forms are relatively rare (38%). The rate of coronary abnormalities was elevated, in comparison to other series even though 1/3 of patients receiving IVIG had doubtful diagnosis of KD. The IVIG resistance rate was 20%. Factors associated with IVIG resistance in our population are currently analysed Acknowledgements: To the French KD study group Supported by a grant from the French ministry of health: PHRCN2009 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3534